The slave dancer - Fox, Paula (New York : Laurel-Leaf Books, 1975)
Kidnapped by the crew of an Africa bound ship, a thirteen-year-old boy discovers to his horror that he is on a slaver and his job is to play music for the exercise periods of the human cargo.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
Book Links (A.L.A.), July 1995.
Booklist, October 2008.
Bulletin (Center for Children's books), August 2004.
Keywords: Slave trade -- Juvenile fiction; Historical fiction; Slave trade -- Fiction; Historical fiction; Slave trade -- Fiction